Sida szechuensis Matuda (Malvaceae), one new species for the flora of Vietnam - Xuyen, Do Thi (Academia Journal of Biology, 2014)
Sida szechuzensis Matsuda (Malvaceae) is a new record for the flora of Vietnam. Its especial characters were: herb; petioles and pedicels always with thick stellate hairs; leaves penninerved; stipules not different, filiform; flowers axillary, solitary or in panicle; calyx campanulate, with 5 triangular lobes; corolla yellow or pale orange, with cuneate petals, mostly more or less oblique; staminal column ca. 5 mm, hirsute with long hairs; ovary with stellate hairs; styles over 7; mericarps outside prominently reticulately veined, short-awned; seeds reniform, dark brown or black, with white hairs. It is close to S. rhombifolia L. but differs from it in leaves with scattered stellate hairs on the upper face, thick stellate hairs on the under face; calyx with thick minute stellate hairs; staminal column with long hairs, style glabrous. The specimens were collected in the Hagiang province (Quanba district).